Air conditioner - TOSHIHIKO OBANA; HIROKAZU TANAKA (2016)
The utility model provides a fin cast heat exchanger and air conditioner. Water heat exchanger (51) add hydrothermal fin cast heat exchanger through carry out the heat exchange between refrigerant and water. Water heat exchanger (51) include: many pieces fin (52) are dull and stereotyped shape and separate each other and arrange, and multiseriate piping (53), run through many pieces of fins (52) and extend to the configuration is at perpendicular to fin (52) and each other in parallel arrangement's a plurality of virtual plane (210, 220). Multiseriate piping (53) contain the refrigerant piping (53m) that makes the logical water piping (53n) of rivers and make the refrigerant circulation. Each fin (52) are formed by the integrated plate material on the array orientation of virtual plane (210, 220) respectively. According to this kind of structure, can provide can be with the fin cast heat exchanger and the air conditioner of low cost manufacturing.